POLYGAMY SEMINARS: BUILDING MASCULINITY VIA LIBIDINAL ECONOMY - Karunia Haganta; Firas Arrasy; Siamrotul Ayu Masruroh (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2022)
This paper discusses polygamy seminars with three critical perspectives: religious commodification, hegemonic masculinity, and libidinal economics. In terms of religious commodification, polygamy seminars as a religious activity held in many places in Indonesia with quite expensive costs are economically beneficial. Regarding Raewyn W. Connell’s masculinity theory, polygamy seminars can be read as activities closely related to masculinity and femininity. The libidinal economic perspective of Jean Francois Lyotard helps see the relationship between religious commodification, desire, and capital in polygamy seminars. This article is an analytical descriptive study with quite extensive empirical data.